Typical configuration analysis of a modular reconfigurable cable-driven parallel robot. (6th March 2019) - Zhao, Tao; Zi, Bin; Qian, Sen; Yin, Zeqiang; Zhang, Dan
To obtain better flexibility and multifunction in varying practical applications, several typical configurations of a modular reconfigurable cable-driven parallel robot are analyzed in this article. The spatial topology of the modular reconfigurable cable-driven parallel robot can be reconfigured by manually detaching or attaching the different number of modular branches as well as changing the connection points on the end-effector to satisfy diverse task requirements. The structure design of the modular reconfigurable cable-driven parallel robot is depicted in detail, including the design methodology, mechanical description, and control architecture. The inverse kinematics and dynamics of the modular reconfigurable cable-driven parallel robot considering diverse configurations are derived according to the vector closed rule and Lagrange method, respectively. The numerical simulation and related experiments of a typical configuration are achieved and analyzed. The results verify the effectiveness and feasibility of the inverse kinematics and dynamics models for the modular reconfigurable cable-driven parallel robot.